Conformation‐specific anti‐tau antibodies distinguish human tauopathies. (20th December 2022) - Hitt, Brian D; Yang, Ting; Beaver, Joshua D.; Shang, Ping; Joachimiak, Lukasz A; White, Charles; Diamond, Marc
Abstract: Background: Neurodegenerative tauopathies are defined by progressive brain accumulation of tau aggregates, and include Alzheimer disease (AD), progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), and Pick disease (PiD). Tau is an intrinsically disordered protein, yet it adopts diverse, highly ordered amyloid assemblies in disease states. These may amplify within cells by acting as "seeds, " or templates for their own replication. Evidence suggests that tau assemblies transfer between cells of the brain, which has inspired the development of immunotherapies that are in clinical trials. Analyses by cryo‐EM of insoluble tau filaments from tauopathies have revealed distinct fibril core structures, but these are not readily distinguished by immunohistochemistry. The tau repeat domain (RD) consists of three or four repeated segments and contains the amino acids comprising each tau filament core. The RD is required for tau assembly and has a different conformation in seed‐competent tau than in inert tau. Antibodies specific for distinct RD conformations have promise as diagnostic and therapeutic agents. Method: We generated novel anti‐tau monoclonal antibodies against structurally defined synthetic linear peptide epitopes predicted to be exposed in seed‐competent tau. We employed a screening protocol using biosensor cell‐based seeding assays to select antibodies for sensitivity and specificity in binding soluble tau seeds from AD and non‐AD tauopathies. Result: Two antibodies, MD2.2 and MD3.1, preferentially bind soluble tau seeds versus inert tau monomer, and distinguish seeds in AD and PSP from those of CBD and PiD. They stain tauopathy brain tissue with a pattern distinct from that of AT8. Conclusion: We have generated novel anti‐tauRD antibodies with specificity for seed‐competent conformations and which distinguish tauopathies. These may be valuable for biochemical and neuropathological investigation of tauopathies and may also improve development of immunotherapy for AD and PSP.